The Study of the Strength Properties of Galvanized Iron (GI) Fiber Reinforced Concrete - Sristi Das Gupta; MD Shah Newaz Aftab Chayon; Chaity Karmaka; Hasan Mohammad Zakaria (Journal of the Civil Engineering Forum, 2020)
The use of concrete with randomly distributed metallic or non-metallic fiber is now prominent in concrete engineering and metallic fiber has been reported to have a better contribution to concrete mechanical properties. The utilization of locally available galvanized iron or metallic fiber as a bridging material which is a new technique in Bangladesh has the ability to surprisingly improve concrete physical properties. This research was, therefore, conducted to compare the concrete performance of GI fiber and steel fiber using previous literature as well as the suitability of GI fiber as a supplant to steel fiber in the concrete industry. This was achieved through the evaluation of the compression, tension, and brittleness of concrete with ‘Galvanized Iron’ fiber using several cutting lengths of 20 mm and 40 mm with multiple mix proportions including 1.0%, 1.5%, 2.0%, and 2.5% by volume of the concrete. The results showed the fiber with a large cut length of 40 mm and proportion lesser than 2.5% performed well than 20 mm with proportion 2% in reference to the plain concrete. Moreover, the incorporation of a 2.0% proportion of galvanized iron fiber with 40 mm length was observed to have exhibited crowning increment for both concrete compression and tension by 16.1% and 89.2% correspondingly contrasted to the control specimen. A further increase in the percent of fiber content 2% led to a reduction in the compression and tension for both 20 mm and 40 mm lengths while a significant reduction in brittleness for galvanized iron fiber reinforced concrete was observed in contrast to the control specimen. Furthermore, the inclusion of 1.0%–2.5% GI fiber with a 40 mm length reduced concrete brittleness by 56.9% - 65.5 % in comparison with the control specimen. Therefore, the inclusion of galvanized iron (metallic) to enhance the physical properties of concrete was deduced to be one of the startling stratagems